การพัฒนาระบบรองรับการสะเทือนแบบควบคุมด้วยสนามแม่เหล็กไฟฟ้า - ปรัชญ์ แจ่มแจ้ง (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
When a vehicle moves on a surface, there is always some vibration. Suspension system affects the efficiency of vehicle driving and controlling. The development of electromagnetic - controlled suspension system is applicable to various kinds of vehicles with the flexibility of the adjustment of suspension styles. It is also accurate by using digital processing unit. In addition, it has less mechanical wear than conventional suspension systems. This thesis presents the design of shock absorber system controlled by electro-magnetic field similar to maglev. The purpose of this thesis is to develop a suspension system suitable for different types of vibration and having higher driving efficiency. The system makes use of permanent magnet movement in a solenoid. The solenoid sends signals to a digital processing unit. Then the processing unit sends signals to an amplifier through a digital-to-analog converter to set the required voltage. The amplifier receives analogue signal which is varied to feed the solenoid. As a result, a variable force is created by moving magnet inside the solenoid. The processing unit receives an input signal representing the variation of the surface model. The signal representing the force between magnet and vehicle chassis is calculated to provide the appropriate force between magnet and vehicle chassis. The output signal is sent to the digital-to-analog converter and fed to the amplifier. The designed suspension system can also set an initial force between magnet and vehicle chassis at the processing unit. It is very useful to be able to adjust the chassis’s height according to different driving situations. Results of surface models of different geometries with variable heights can confirm the response of this developed suspend system.